A contemporary review of Grupo Austral's housing typologies for Argentina's countryside. (4th March 2021) - Collo, Florencia; Yannas, Simos
Abstract : The paper reviews four housing typologies designed by Grupo Austral in 1939 for rural regions of Argentina. The design of each dwelling was adapted to the different climatic regions of the country, which range from warm subtropical to cold desert. Grupo Austral's design proposals demonstrate an outstanding environmental awareness. In this paper, the design features of these houses are evaluated against present knowledge and advanced environmental simulation tools. The original building specifications are found to compare very well with contemporary environmental design practices.